2016
DOI: 10.1007/s10658-016-0939-1
|View full text |Cite
|
Sign up to set email alerts
|

Pathotypes of Plasmodiophora brassicae causing damage to oilseed rape in the Czech Republic and Poland

Abstract: Winter oilseed rape (Brassica napus) is an important crop in the Czech Republic and Poland. Clubroot disease caused by the pathogen Plasmodiophora brassicae is a serious and still-growing problem for oilseed rape growers in both countries. The aim of this study was to evaluate the pathotype composition of P. brassicae populations from the Czech Republic and Poland, according to the three evaluation systems, and to determine soil inoculum loads for representative fields via traditional end-point PCR as well as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 21 publications
(50 reference statements)
0
20
0
Order By: Relevance
“…Physiological specialization has long been known to occur in P. brassicae [ 6 ], with pathotypes of the pathogen varying in their ability to infect specific host crops. Previous studies in European countries have revealed variations in pathotype distributions across different countries [ 7 , 8 , 9 , 10 ]. Pathotype 1 (P1) and Pathotype 3 (P3) or ECD 16/31/31 and 16/14/31 as classified on the differentials of Somé et al [ 11 ] and the European Clubroot Differential [ 12 ], respectively, are predominant in central Europe.…”
Section: Introductionmentioning
confidence: 99%
“…Physiological specialization has long been known to occur in P. brassicae [ 6 ], with pathotypes of the pathogen varying in their ability to infect specific host crops. Previous studies in European countries have revealed variations in pathotype distributions across different countries [ 7 , 8 , 9 , 10 ]. Pathotype 1 (P1) and Pathotype 3 (P3) or ECD 16/31/31 and 16/14/31 as classified on the differentials of Somé et al [ 11 ] and the European Clubroot Differential [ 12 ], respectively, are predominant in central Europe.…”
Section: Introductionmentioning
confidence: 99%
“…Infection in oilseed brassicas has been reported worldwide (Saharan, 1993;Bhattacharya et al, 2014;Řičařová et al, 2016;Xue et al, 2017), as well as in B. juncea vegetables in China (Xue et al, 2017) and B. juncea crops in India (Chattopadhyay and Bagchi, 1989;Bhattacharya et al, 2014). A major first epidemic of clubroot occurred in the early 1980s in India (Laha et al, 1985), where disease incidence ranged from 30% on B. juncea to 70% on B. rapa (Chattopadhyay and Bagchi, 1989).…”
Section: Clubrootmentioning
confidence: 99%
“…Infection in oilseed brassicas has been reported worldwide (Saharan, 1993; Bhattacharya et al, 2014; Řičařová et al, 2016; Xue et al, 2017), as well as in B . juncea vegetables in China (Xue et al, 2017) and B .…”
Section: Diseases Affecting B Junceamentioning
confidence: 99%
“…The 25.5 Mb genome sequence of P. brassicae single spore isolate e3 was presented for the first time a few years ago [7]. Internationally, the spread of P. brassicae has increased rapidly in spring OSR (canola) in Canada [8,9], North Dakota [10], Finland [11] and Latin-America [12], and in winter OSR in the UK [13], Germany [14], Poland, [15,16], Czech Republic [17], China [18], and other countries.…”
Section: Introductionmentioning
confidence: 99%